(untitled) (International Congress on Economics, Management and Business Studies, 2026)
Rapid changes in consumer preferences, technological development, and market volatility have significantly increased uncertainty in the service sector. Under such conditions, adaptability becomes a critical capability for service enterprises seeking sustainable performance. This paper examines adaptability as an independent strategic and organizational concept in the service sector. Unlike traditional competitiveness-oriented studies, the research focuses on how service enterprises adapt to changing market conditions through organizational flexibility, strategic responsiveness, and learning capacity. Using a conceptual and analytical approach, the study proposes a framework of service enterprise adaptability and discusses its implications for long-term performance. The results contribute to service management research by positioning adaptability as a central category in service sector analysis.